Existence and uniqueness results for q-fractional difference equations with p-Laplacian operators - Mardanov, Misir J.; Mahmudov, Nazim I.; Sharifov, Yagub A. (Springer International Publishing Ag, 2015)
In this paper, we consider the following two-point boundary value problem for q-fractional p-Laplace difference equations. New results on the existence and uniqueness of solutions for q-fractional boundary value problem are obtained. These results extend the corresponding ones of ordinary differential equations of integer order. Finally, an example is presented to illustrate the validity and practicability of our main results.
Keywords: fractional differential equations; existence; fixed point